2013
DOI: 10.1039/c3dt51004b
|View full text |Cite
|
Sign up to set email alerts
|

C–H functionalization: thoroughly tuning ligands at a metal ion, a chemist can greatly enhance catalyst's activity and selectivity

Abstract: This brief essay consists of a few "exciting stories" devoted to relations within a metal-complex catalyst between a metal ion and a coordinated ligand. When, as in the case of a human couple, the rapport of the partners is cordial and a love cements these relations, a chemist finds an ideal married couple, in other words he obtains a catalyst of choice which allows him to functionalize C-H bonds very efficiently and selectively. Examples of such lucky marriages in the catalytic world of ions and ligands are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(78 citation statements)
references
References 335 publications
3
74
1
Order By: Relevance
“…We proposed and developed a simple method for analysis of alkyl hydroperoxides generated in various alkane oxidations in solutions [11][12][13][247][248][249][250][251][252]). A chemist can find that, if the direct injection of a reaction sample into the chromatograph gave comparable amounts of cyclohexanol and cyclohexanone ( Figure 16, Figure 17a), the reduction of the sample with PPh 3 prior to GC analysis led to the noticeable predominance of the alcohol (Figure 17b).…”
Section: Detection and Determination Of Alkyl Hydroperoxides Comparinmentioning
confidence: 99%
See 1 more Smart Citation
“…We proposed and developed a simple method for analysis of alkyl hydroperoxides generated in various alkane oxidations in solutions [11][12][13][247][248][249][250][251][252]). A chemist can find that, if the direct injection of a reaction sample into the chromatograph gave comparable amounts of cyclohexanol and cyclohexanone ( Figure 16, Figure 17a), the reduction of the sample with PPh 3 prior to GC analysis led to the noticeable predominance of the alcohol (Figure 17b).…”
Section: Detection and Determination Of Alkyl Hydroperoxides Comparinmentioning
confidence: 99%
“…This review is devoted to functionalization of carbon-hydrogen bonds [1][2][3][4][5][6][7][8][9][10][11][12][13] in various organic compounds, which is a very important process both from academic and practical point of view. Replacing hydrogen atoms in carbon-hydrogen compounds by functional groups X leads to valuable functionalized C-X compounds (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cyclohexane gives minimum number of oxidation products which are easily identified by the GC method. As demonstrated previously in other oxidations [19,[59][60][61][62][63][64][65][66][67][68], if the direct injection of a reaction sample into the chromatograph gave comparable amounts of cyclohexanol and cyclohexanone, the reduction of the sample with PPh3 (or certain sulfides) prior to GC analysis in many cases led to the noticeable predominance of the alcohol (Figure 8). The comparison of the results obtained before and after the reduction clearly indicated that cyclohexyl hydroperoxide was formed as the main primary product.…”
Section: Catalytic Oxidation Of Alcohols and Hydrocarbonsmentioning
confidence: 79%
“…In order to determine concentrations of all cyclohexane oxidation products the samples of reaction solutions after addition of nitromethane as a standard compound were in some cases analyzed twice (before and after their treatment with PPh3) by GC (LKhM-80-6 instrument, columns 2 m with 5% Carbowax 1500 on 0.25-0.315 mm Inerton AW-HMDS; carrier gas argon) to measure concentrations of cyclohexanol and cyclohexanone. This method (an excess of solid triphenylphosphine is added to the samples 10-15 min before the GC analysis) was proposed by one of us earlier [19,[59][60][61][62][63][64][65][66][67][68]. Attribution of peaks was made by comparison with chromatograms of authentic samples.…”
Section: Oxidation Of Alcohols and Hydrocarbons With Peroxidesmentioning
confidence: 99%
“…Indeed, oxidation of alkanes has been the object of considerable research [69][70][71][72][73][74][75][76][77][78], but still constitutes a serious challenge to modern chemistry, owing to the high inertness of these substrates. Currently, alkanes are mainly applied as fuels but it would be desirable to direct their application to the synthesis of organic products of a high added value.…”
Section: Introductionmentioning
confidence: 99%